Validation of Hydraulic Mechanism during Blowout Trauma of Human Orbit Depending on the Method of Load Application - Marcin A. Zmuda Trzebiatowski; Paweł Kłosowski; Andrzej Skorek; Krzysztof Żerdzicki; Paweł Lemski; Mateusz Koberda (Applied Bionics and Biomechanics)
The more we know about mechanisms of the human orbital blowout type of trauma, the better we will be able to prevent them in the future. As long as the buckling mechanism’s veracity is not in doubt, the hydraulic mechanism is not based on equally strong premises. To investigate the correctness of the hydraulic mechanism’s theory, two different methods of implementation of the hydraulic load to the finite element method (FEM) model of the orbit were performed. The intraorbital hydraulic pressure was introduced as a face load applied directly to the orbit in the first variant, while in the second one the load was applied to the orbit indirectly as a set of nodal forces transferred from the external surface of the eyeball via the intraorbital tissues to the orbital walls within the contact problem. Such an approach is aimed at a better understanding of the pattern for the formation of blowout fractures during the indirect load applied to the orbital bones. The nonlinear dynamic analysis of both numerical models showed that the potential fracture was observed in the second variant only, embracing a relatively large area: both medial and lower wall of the orbit. Interestingly, the pressure generated by the intraorbital entities transferred the energy of the impact to the orbital sidewalls mainly; thus, the nature of the mechanism known as the hydraulic was far from the expected hydraulic pressure. According to the eyeball’s deformation as well as the areas of the greatest Huber-Mises-Hencky (H-M-H) stress within the orbit, a new term of strut mechanism was proposed instead of the hydraulic mechanism as more realistic regarding the investigated phenomenon. The results of the current research may strongly influence the development of modern implantology as well as affect forensic medicine.